THE PROCESSES OF IMPROVING PUBLIC SERVICE IN THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
In this scientific work, scientific research aimed at studying foreign experience in introducing effective technologies into the national civil service system is considered as one of the topical issues of today. It is also devoted to clarifying the foundations of reforms carried out in the field of modernizing the civil service in New Uzbekistan, as well as creating a compact and efficient management system that serves citizens through the transformation of central bodies.